Constructing Indonesian Composite Infrastrcuture Index using Principal Component Analysis. - FIRMAN HERDIANSAH; Farah Pangestuty (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2022)
This article aims to develop Indonesia's economic infrastructure indices, including transportation, telecommunications, education, and financial. The index employs indicators from 2018 at the regency level using Principal Component Analysis (PCA) to aggregate the index for each infrastructure component. The result shows that the use of PCA to reduce the data dimensions is quite effective in producing indices because the principal components are very representative of the data set as a whole.